Metformin and Insulin Treatment Influence on Monoamine Oxidase Activity in Diabetes Mellitus Type 2 - Ruaa Hassan K. Alani (Journal of Global Pharma Technology, 2018)
The influence of anti-hyperglycemic drugs (Metformin, insulin) on the activity of Monoamine oxidase in the sera of diabetes millets type2 .This study included 54 volunteers, 36 with diabetes millets type 2, treated with Metformin, and metformin + insulin, and18 healthy volunteers without endocrinal diseases represent the control group. Activity of Monoamine oxidase, body mass index, fating blood glucose, glycosylate haemoglobin, and lipid profile levels respectively were examined in this study. The results revealed significant decrease in the levels of BMI, FBG, and lipid profiles in the two groups as compared to control. Monoamine oxidase showed different in the patients groups as compared to healthy group. As conclusion this study showed different effect of treatment on the biochemical parameters and enzyme activity and this effect may decrease the occurrence of diabetes complication including neuropathy (neurodegredation diseases (Parkinson, and Alzheimer diseases) and increases patients life.